Changes in wage inequality - Machin, Stephen; van Reenen, John (London, 2007)
"We examine trends in wage inequality in the US and other countries over the past four decades. We show that there has been a secular increase in the 90-50 wage differential in the US and the UK since the late 1970s. By contrast the 50-10 differential rose mainly in the 1980s and flattened or fell in the 1990s and 2000s. We analyze the reasons for these trends and conclude that a version of the skill biased technical change hypothesis combined with institutional changes (the decline in the minimum wage and trade unions) continues to offer the best explanation for the observed patterns of change. "